The Body of Il Duce: The Myth of the Political Physicality of Mussolini in Marco Bellocchio’s Vincere - Luceri, Marco (Cinema: Journal of Philosophy and the Moving Image, 2012)
In 2009, Marco Bellocchio made the film Vincere, which tells the tormented relationship between Benito Mussolini and Ida Dalser. The film not only retraces Mussolini’s personal life, but also his ascent to power. In the narration of this political aspect, Bellocchio, thanks to his collaboration with the actor Filippo Timi, reinterprets and sheds new light on one of the most interesting aspects of the biography of il Duce: the importance of the mediatic use of his body as a political statement. By way of some important stylistic choices, the director shows that these media images are nothing but illusions hiding the true, dark and perverse side of Mussolini’s character.